An integrated socio-institutional model for visual arts development and policy formulation in Medan, Indonesia - Zulkifli Zulkifli; Anam Ibrahim; Azmi Azmi; Barli Kifli; Lanang Riyadi (Institut Seni Indonesia Surakarta, 2026)
Visual art activities in Medan City, Indonesia, have a long-standing history, yet over the past decade, the ecosystem has experienced a significant decline, indicated by decreasing artist participation, a lack of periodic exhibitions, and underutilized infrastructure. Previous studies have primarily focused on the creative aspects of local cultural identity, leaving a critical research gap regarding the socio-institutional factors and policy frameworks required to sustain the arts ecosystem. This study employs a mixed methods descriptive-qualitative approach to formulate an evidence based development model and policy concept for Medan. Data were collected through observations, surveys of 36 practitioners, and in-depth interviews with 12 key stakeholders. Empirical findings reveal a severe coordination gap among artists, public appreciators, and local government, as well as a lack of physical and digital infrastructure. To address this, we propose an Integrated Socio-Institutional Model that synergizes the domains of creation, presentation, and art research. The novelty of this research lies in shifting the focus from isolated artistic production to a comprehensive, interconnected ecosystem approach that includes digital integration (NFTs). The theoretical contribution expands the sociology of art by embedding municipal policy frameworks, while the practical contribution provides a hierarchical policy blueprint (prioritizing the establishment of a coordinating body and the revitalization of creative centers) to enhance the sustainability and economic impact of Medan's visual arts scene.